KUALITAS PELAYANAN DAN PENGARUHNYA TERHADAP KEPUASAN DAN LOYALITAS YANG SYAR’I PEMEGANG POLIS ASURANSI SYARIAH - Wuryanti Koentjoro (Jurnal Ekonomi dan Bisnis, 2009)
The purpose of this article is to investigate the effect of perception’s service quality, and priceon satisfaction and customer’s loyalty at Shariah life insurance in Central Java Province. Thepopulation are Shariah life insurance staff The respondents are chosen by using accidentalsampling techniques. The data collected from 140 respondents and analysed by statisticaltool of structural equation modeling (SEM). The result showed that : First, perception of servicequality produced a positive significant impact on satisfaction. Second, satisfaction waspositive and significantly associated with customer’s loyalty. Third, the service quality was directlyrelated to customer’s loyalty, but the effect of service quality on customer’s loyalty morethan satisfaction as intervening variable with estimate value 0,767 if compared the directlyrelated service quality on loyalty, with value 0,277 Theoretical found that the conventionalServQual is a part from Shariah insurance study, the Shariah insurance as an alternative forcustomer will be faithful to the religion norm in accordance with Shariah principles. The empiricalfound that as Shariah insurance customers, the customers have already executed thereligion norm in accordance with Al.Quran at An-Nisa:9. Studies found that the society’s Interestto buy Shariah life insurance policy and the insurance commitment to the risk protectingare low, finally the society commitment toward life insurance decreases.Key words : Service Quality/Khidmah, with The Syar’I Satisfaction/Qona’ah and Customer’sLoyalty/Al-wala’